MOTIVATION OF CRIMINAL ACTIVITIES OF PERSONS COMMITTING HATE CRIMES AND PREVENTION STRATEGIES - Muraševs, Gints Georgs; Vilks, Andrejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The study aims to analyze the motivation of hate crime perpetrators to commit a hate crime and to analyze the possibilities for preventing hate crime in the context of education. The study's tasks are to find out what motivating factors a person has in committing hate crimes aswell as analyze the role of hate as an emotion in committing crimes. The role of education and the opportunities offered through education to reduce hate crime will also be assessed. The focus of the study is based upon the increasing focus of the European Union on reducing hate crimes in the Member States and the high impact of education on personal development, which can be a determining factor in a person's tendency to commit crimes. The results of the study will be able to be used in educational institutions to gain more detailed insights into factors motivating hate crimes so that pedagogical approaches can be developed and improved in order to reduce the tendency of individuals to commit hate crimes. The study will use the descriptive method to describe the personality and motivation of hate criminals to commit hate crimes, as well as a data analysis to draw conclusions about factors motivating crime.